The Role of the Cooperative Script Method in Developing Self-Confidence and Public Speaking Skills Among Madrasah Ibtidaiyyah Student - Isa Anshori; M. Rofiqul Majid; Sufatul Fitria; Ghazwu Fikril Haq (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2024)
The Cooperative Script Method (CSM) has gained prominence as an instructional approach that enhances key student skills, including self-confidence and public speaking abilities. This study aimed to investigate the impact of CSM on students' self-confidence and public speaking skills. The research was conducted at Madrasah Ibtidaiyah Al-Anwar Sarang using a quantitative approach, involving 37 purposively selected fifth-grade students. Data were collected through questionnaires, complemented by in-depth observations, and analyzed using linear regression and the Sobel test. The results indicated that CSM significantly enhances students' self-confidence (p